2018
DOI: 10.6004/jnccn.2018.7023
|View full text |Cite
|
Sign up to set email alerts
|

Management of Primary Ovarian Insufficiency Symptoms in Survivors of Childhood and Adolescent Cancer

Abstract: Cancer treatments can damage the ovaries, causing primary ovarian insufficiency (POI), a condition associated with numerous sequelae that impact long-term quality of life. This article systematically reviews the literature on the prevalence, surveillance, and treatment of POI in survivors of pediatric and adolescent and young adult (AYA) cancers. A systematic review of the literature was conducted in January 2018 through a search of Medline, Embase, Web of Science, and SCOPUS, alongside the screening of releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 84 publications
1
43
0
Order By: Relevance
“…Several studies of childhood cancer survivors demonstrate impairment in sexual and reproductive functions. [ 15 , 65 , 66 ] This include different types of sexual dysfunctions, negative impact on intimate relations, and the emotional consequences of living with threatened or actual infertility. There is, however, a lack of large-scale methodologically rigid studies on the prevalence of these issues, and of the factors associated to them.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of childhood cancer survivors demonstrate impairment in sexual and reproductive functions. [ 15 , 65 , 66 ] This include different types of sexual dysfunctions, negative impact on intimate relations, and the emotional consequences of living with threatened or actual infertility. There is, however, a lack of large-scale methodologically rigid studies on the prevalence of these issues, and of the factors associated to them.…”
Section: Discussionmentioning
confidence: 99%
“…This process makes PGCs extremely sensitive to the effects of CT and RT. Evidence suggests that the incidence of POI in female survivors of childhood and adolescent cancer is 2.1-82.2% [21]. RT can be more damaging to ovarian tissue than CT because apart from being particularly irreversibly toxic to oocytes [22,23], its off-target effects can also affect the surrounding tissue [24].…”
Section: Tumor Therapymentioning
confidence: 99%
“…Of the few identi ed causes, iatrogenic conditions account for a large proportion (~ 65%) of cases [12], including radiotherapy (RT), chemotherapy (CT), and drugs for various autoimmune diseases [13,14]. The incidence of iatrogenic POI has been reported to be growing owing to increasing survival rates following diverse cancer treatments [15][16][17]. In addition, accumulating evidence has revealed that women with endometriosis or a history of pelvic surgery are more likely to have severely compromised ovarian function, including POI [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental, artificial human ovary technology may be the only option to preserve and restore fertility in some patients when other fertility preservation and restoration options are contraindicated, infeasible, unavailable, rejected or unsuccessful . Contraindications of the major options for female fertility preservation and restoration are listed in Table .…”
Section: Significance: Importance Of Artificial Human Ovary For Patientsmentioning
confidence: 99%
“…Although experimental, artificial human ovary technology may be the only option to preserve and restore fertility in some patients when other fertility preservation and restoration options are contraindicated, infeasible, unavailable, rejected or unsuccessful. [17][18][19][20][21][22][23] Contraindications of the major options for female fertility preservation and restoration are listed in Table 1. Although experimental, three major categories of patients (age <40 years) may benefit from artificial ovary technology to preserve and restore fertility:…”
Section: S I G Nifi C An Ce: Imp Ortan Ce Of Artifi Cial H Uman Ovamentioning
confidence: 99%